# Using prope

Given: There are two sets A and B

To prove: A – (A B) = A – B

Take L.H.S

A – (A B)

= A (A B)’

{ A – B = A B’}

= A (A B’)’

= A (A’ B’)

{ (A B)’ = A’ B’}

= (A A’) (A B’)

{ Distributive property of set:

(A B) (A C) = A (B C)}

= Φ (A B’)

{ A A’ = Φ}

= A B’

= A – B

{ A – B = A B’}

= R.H.S

Hence Proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Let A = {a, b, c,RS Aggarwal - Mathematics

If A and B be twoRS Aggarwal - Mathematics

(i) If A <span laRS Aggarwal - Mathematics

Using propeMathematics - Exemplar

If A and B are twRS Aggarwal - Mathematics

In a town of 10,0RS Aggarwal - Mathematics

If A and B are twRS Aggarwal - Mathematics

If <a name="MTBlaRS Aggarwal - Mathematics

If n(A) = 3 and nRS Aggarwal - Mathematics

For any sets A, BRS Aggarwal - Mathematics